The evolution of the Pure Community Module: How lessons learned from national, regional, and subject-focused use cases have been used to support inter-institutional collaboration - Toon, James (Procedia computer science, 2022)
This abstract provides an update on development and implementation progress of the Pure community module in the 5 years since the initial launch of the service. The paper revisits the conclusions of our 2018 presentation [1], providing updates on the ‘future developments’ and encourages a discussion of the complexities in supporting multi-institutional collaborations. In addition, we will provide an overview of some key challenge areas we have been working on together with community customers and community owners (technical and operational).